How to Use Challenge-Based Learning for the Acquisition of Learning to Learn Competence in Early Childhood Preservice Teachers: A Virtual Archaeological Museum Tour in Spain - Abril-López, Daniel; López Carrillo, Dolores; González-Moreno, Pedro Miguel; Delgado-Algarra, Emilio José (Frontiers in Education, 2021)
This article presents the research results in relation to an interdisciplinary teaching innovation project—Teaching and Learning of Social Sciences, and Teaching and Learning of Natural Sciences—with Early Childhood Preservice Teachers (ECPT) at the University of Alcalá (Spain) during the academic year 2020-2021. The main objective was to improve the learning to learn competence during a virtual tour at the Community of Madrid Regional Archaeological Museum (MAR) (Alcalá de Henares, Spain) in the context of the pandemic caused by Covid-19, using the challenge-based learning approach, and e/m-learning tools (Blackboard Learn, Google Forms and QR codes, websites, YouTube). In order to ascertain the level of acquisition of this competence in those teachers who were being trained, their self-perception—pre-test–post-test—of the experience was assessed through a system of categories adapted from the European Commission. ECPT worked in small groups ten challenges and one storytelling cooperatively with its university professors to solve prehistoric questions related to current situations and problems. Subsequently, two Early Childhood Education teachers from a school in Alcalá de Henares reviewed the proposals and adapted them for application in the classroom of 5-year-old boys and girls. The results show, as well as an outdoor experience at the Museum of Guadalajara (Spain) over three academic years (2017–2018, 2018–2019, and 2019–2020), a certain improvement in this competence in Early Childhood Preservice Teachers; an evaluation rubric verified the results of self-perception. Second, we highlight the importance of carrying out virtual museum tours from a challenge-based learning for the promotion, understanding and development of big ideas, essential questions, challenges and activities on socio-economic, environmental and emotional knowledge, skills and attitudes. Third, this experience shows the insufficient educational adaptation of the virtual museum tour to the early childhood education stage from a technological and didactic workshops point of view; but there is a diversity of paleontological and archaeological materials, and a significant socio-critical discourse.